Letter - Schlossberg, Joseph, 1975-
028-0145-001 Amalgamated Clothing Workers of America Affiliated with the American Federation of Labor 15 Union Square Office of the Secretary New York, N. Y. TELEPHONE: ALGONQUIN 4-6500 OFFICIAL PUBLICATION "THE ADVANCE" Sidney Hillman, General President. Joseph Schlossberg, General Sec'y-Treas. General Executive Board: Dorothy J Bellanca Hyman Blumberg Joseph Catalanotti Abraham Chatman Louis Hollander Jack Kroll Leo Krzycki Samuel Levin Anzuino D. Marimpietri Abraham Miller Sidney Rissman Frank Rosenblum Stephan Skala Charles Weinstein Murray Weinstein November 19-1936. Sir Walter Citrine, Secretary British Trade Union Congress, Transport House, London, England. Dear Comrade Citrine: I am enclosing herewith a draft for five pounds, which represents a donation of $25.00 received by us from our local organization in St. Paul, Minnesota for the Solidarity Fund for the Spanish Workers. I know that the workers' families in Spain are in need of all the help that can be given to them and I am glad that we have been able to extend some help. Besides the $5000.00 which we forwarded to you sometime ago, additional donations were handed over by our local union to the International Ladies' Garment workers' Union. The International since then has closed its fund. I am, therefore, forwarding this amount direct to you. Fraternally yours, Joseph Schlossberg, General Secretary-Treasurer. JS:Q 292/946/28/145